Gentiles, Jews and heretics: non-Christians in the councils of Elvira (306) and Arles (314) - de Carvalho Júnior, Macário Lopes (Romanitas - Revista de Estudos Grecolatinos, 2013)
The ecclesiastical councils of Elvira (306) and Arles (314) published a set of rules that disciplined the behavior and conduct of Christians. Part of this legislation concerns relations between Christian and non-Christians throughout local communities represented in those assemblies. Polytheists’, in this laws called gentile, Jews and heretics, are categories that emerge out of reading these rules à rebours. Relations established between those who were and were not Christians help us to understand this period of consolidation of Christianity and the growing legislation on the private life of individuals, a Christian innovation.
Keywords: Council; Council Legislation; Polytheists; Jews; Heretics